Analysis of Biology Learning Resources and Materials in PJBL, PBL, and Deep Learning in Class X in Biology Teachers and Students of SMA Negeri 2 Lubuk Pakam - Mohonia Sabarito Sitohang; Wila Nurlisa Putri; Yuliani Sueng; Risalina Septiani Br Tarigan; Cynthya Elizabet Pasaribu; Rizal Mukra; Widya Arwita (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
The success or failure of the learning process in schools is greatly influenced by teachers in their choices. Teaching materials are materials or information used by teachers for their learning. The purpose of this study was to determine the perception, analyze the availability, and analyze the difficulties of teachers and students in relation to PJBL, PBL, and learning resources and materials that support deep learning. This study is based on qualitative research methods. This method directly distributes questionnaires to 20 students of class X MIA and four biology teachers, at SMA Negeri 2 Lubuk Pakam. Data were collected using observation, interview and document techniques. The results obtained are explained by explaining the observations in the discussion. Teachers try to provide various learning resources, including textbooks, science magazines, and laboratory videos. Students believe that the three methods of learning materials are relevant to daily activities and can help them understand the material. However, there are some problems that have not been resolved. For example, it is difficult to find access to digital learning resources, and there is no variation in teaching.